2017
DOI: 10.1536/ihj.16-244
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Safety of Transulnar Catheterization in Ipsilateral Radial Artery Occlusion

Abstract: SummaryTo investigate the postprocedural cardiovascular events and vascular outcomes, including hand ischemia and neurological compromise, after transulnar (TU) catheterization in ipsilateral radial artery occlusion.Previous randomized trials have shown that the transulnar (TU) approach for coronary angiogram and intervention has safety and outcomes similar to those of the transradial (TR) approach. However, the safety of the TU procedure when ipsilateral radial artery occlusion occurs is unknown.We retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…[1][2][3] The access site is an important determinant of bleeding complications following PCI, 4) and the incidence of bleeding complications is significantly lower in transradial PCI than in transfemoral PCI. 5) Although radial arteries have been widely used in current PCI, including primary PCI, 6) transfemoral PCI remains necessary for complex PCI requiring a !7 Fr guide system such as chronic total occlusion or severely calcified lesions.…”
mentioning
confidence: 99%
“…[1][2][3] The access site is an important determinant of bleeding complications following PCI, 4) and the incidence of bleeding complications is significantly lower in transradial PCI than in transfemoral PCI. 5) Although radial arteries have been widely used in current PCI, including primary PCI, 6) transfemoral PCI remains necessary for complex PCI requiring a !7 Fr guide system such as chronic total occlusion or severely calcified lesions.…”
mentioning
confidence: 99%
“…The pre-procedure angiographic review of the forearm showed that 95.7% of the patients had significant collaterals from the interosseous artery to the distal portion of the radial artery, after the occlusion segment. Thus, blood circulation in the palmar arch and digital vessels was maintained even with the ulnar artery temporarily occluded by the ulnar arterial sheath (33).…”
Section: Comparison Between the Ulnar And Radial Accessesmentioning
confidence: 99%
“…Sýnt hefur verið fram á með allmörgum rannsóknum að almennt er öruggt að fá aeðaaðgang í ölnarslagaeð þegar sveifarslagaeð er stífluð en þessar rannsóknir hafa oftast verið á sjúklingum sem gangast undir kransaeðaþraeðingu. 3,4 Í flestum skráðum tilfellum þar sem sjúklingar hafa fengið blóðþurrðardrep í tengslum við slagaeðaleggi er um að raeða fjölveika gjörgaeslusjúklinga í lostástandi og er dánartíðni há. 2,[5][6][7][8] Áhaettuþaettir fyrir blóðþurrð eftir slagaeðaleggsísetningu eru óljósir.…”
Section: Umraeðaunclassified